Analisis Faktor-Faktor yang Mempengaruhi Pendapatan Driver Transportasi Online (Studi Kasus Driver Go-Jek di Kota Semarang) - Anggit Prayogo; Fitrie Arianti (Universitas Diponegoro, 2020)
The development of science and technology influences the development of transportation technology. GO-JEK is one transportation using development technology. This study aims to analyze the factors that influence GO-JEK Driver's income in Semarang City. The number of points, the average tariff for each order, the flow of work hours, and work experience are the influencing variables. The population in this study is unknown from the authority of the GO-JEK office in Semarang City. Determination of the sample using a minimum sample calculation formula that is equal to 100 GO-JEK Drivers in Semarang city. Samples are taken at simple random. The type of data is primary data. Questionnaire and indepth interview used to collect the data. Multiple linear regression analysis was used in this study. The results showed that the number of points, the average tariff of each order, the flow of working hours, and work experience simultaneously had an influence and significant on income. R2 value is 0.899 means the effect of independent variables on income is 89.9 percent while the remaining 10.1 percent is influenced by other variables outside the equation. Partially, variable number of points, average tariff of each order, and flow of work hours have a positive and significant effect on income while work experience has no effect and is not significant on income but has a positive relationship.